187k views
0 votes
Let u= ln x and v=ln y. Write ln(x^3y^2) in terms of u and v.

Let u= ln x and v=ln y. Write ln(x^3y^2) in terms of u and v.-example-1
User Tor Haugen
by
6.4k points

2 Answers

5 votes

Answer:

A edge

Explanation:

User Daniel Gardiner
by
5.7k points
3 votes

Answer:

a. 3u + 2v

Explanation:

To solve this problem, we need to apply some properties of logarithms. Properties are useful to simplify complicated expressions. Here we need to use a very useful property of logarithms called the logarithm of a product is the sum of the logarithms, that is:


log_(b)(MN)=log_(b)(M)+log_(b)(N)

From the function, it is then true that:


ln(x^(3)y^(2))=ln(x^(3))+ln(y^(2))

The other property we must use is Logarithm of a Power:


log_(b)M^(n)=nlog_(b)M

Then:


ln(x^(3)y^(2))=ln(x^(3))+ln(y^(2)) \\ \\ ln(x^(3)y^(2))=3ln(x)+2ln(y)

Since:


u=ln(x) \\ v=ln(y)

Then:


ln(x^(3)y^(2))=3u+2v

Finally, the correct option is:

a. 3u + 2v

User Blehi
by
6.5k points